SYNTHESIS AND ANTIMICROBIAL EVALUATION OF NOVEL SCHIFF BASES ANALOGUE OF 3-(4-AMINO) PHENYLIMINO) 5- FLUOROINDOLIN-2-ONE. - NIRMAL.R; AJAY BABU.CH; PRASAD RAO. M (International Journal of Pharma and Bio Sciences, 2010)
The synthesis and the in vitro evaluation of antibacterial activity of new schiff bases analogues of 3-(4-Amino) Phenylimino) 5- substituted indolin-2-One are reported. The newly synthesized compounds were characterized by IR, 1H NMR and Mass spectral studies. Representative compounds were screened for antibacterial (Staphylococcus aureus ATCC-9144, Staphylococcus epidermidis ATCC-155, Micrococcus luteus ATCC-4698, Bacillus cereus ATCC-11778, Escherichia coli ATCC-25922, Pseudomonas aeruginosa ATCC-2853, and Klebsiella pneumoniae ATCC-11298) and antifungal (Aspergillus niger ATCC-9029 and Aspergillus fumigatus ATCC-46645) activities by paper disc diffusion technique. The minimum inhibitory concentrations (MICs) of the compounds were also determined by agar streak dilution method.